2011
DOI: 10.1039/c1dt10464k
|View full text |Cite
|
Sign up to set email alerts
|

Urease inhibition and anti-leishmanial assay of substituted benzoylguanidines and their copper(ii) complexes

Abstract: A series of N,N',N''-trisubstituted guanidines (1-6) and their copper(II) complexes, [κ(2)(O,N)-C(6)H(5)CONHC(NHC(6)H(4)Cl)NR](2)Cu(ii) (R = iso-propyl (1a), n-butyl (2a), sec-butyl (3a), tert-butyl (4a), benzyl (5a), and para-tolyl (6a)) were synthesized and characterized using elemental analysis, FTIR and NMR spectroscopy. DFT studies were used to assess the location of the protons in the free ligands. However, calculations have shown that, in all cases, hydrogen bonding from either N-H group gives conformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Agar tube dilution protocol and agar well diffusion methods were used for the preliminary screening of precursors I a – I e and then compounds 1 – 5 against various strains of fungi and bacteria. Following published protocols, the synthesized compounds were also tested for their antioxidant, lipoxygenase, α‐glycosidase and anti‐urease activities.…”
Section: Methodsmentioning
confidence: 99%
“…Agar tube dilution protocol and agar well diffusion methods were used for the preliminary screening of precursors I a – I e and then compounds 1 – 5 against various strains of fungi and bacteria. Following published protocols, the synthesized compounds were also tested for their antioxidant, lipoxygenase, α‐glycosidase and anti‐urease activities.…”
Section: Methodsmentioning
confidence: 99%
“…The data were integrated using the programme SAINT [30] and were corrected for Lorentz and polarization effects. The structure was solved and refined using SHELXS-97 and SHELXL-97 [31]. All the non-H atoms were refined anisotropically.…”
Section: Methodsmentioning
confidence: 99%
“…Murtaza et al 115 demonstrated the synthesis of a series of N , N ′, N ″‐trisubstituted guanidines and their copper(II) complexes. The synthesized compounds have been subjected to the urease inhibition screening.…”
Section: Classes Of Urease Inhibitorsmentioning
confidence: 99%